The Structure – Performance of Indonesian Banking Industry - Setyawan, Mohammad Irwan (2015)
This paper employs the test developed by Berger (1995) to investigate the relationship between concentration and performance for the Indonesian banking market. In this paper, the models incorporate X-efficiency, scale efficiency, and measures of concentration and market share to test the market-power and efficient-structures hypotheses in the Indonesian banking sector. The panel data estimation was used to test the models. These hypotheses have different implications for regulation. The foundation of anti-trust agreement is established on the market-power hypothesis. On the contrary, the efficient-structure hypothesis rejects the view of the anti-trust regulation. A failure to understand this relationship may lead to undesired policy implications.